Is it possible to convert penalty in a post-decision Act? need to rethink Plenary Agreement No 3-2012 - Arrieta Ramírez, Manuel (2016)
The work aims to answer the problem that affects a large sector of the primary crime, petty or bagatelle, where the defendants are deprived of their liberty for breach of the rules of conduct imposed in a suspended sentence in its execution or reserve conviction, basically for nonpayment of the civil repair, in spite of being satisfied such payment but postdated. Therefore, it is proposed that the conversion results viable in execution of a guilty verdict, as well as carrying out a weighing trial between two relevant constitutional principles of the same value and hierarchy, such as the principle of immutability of the judged thing vs. principle of humanity of penalties.